APPLICATION OF GARDENING PROJECT IN KINDERGARTEN - Riska Puspaningrum; Anayanti Rahmawati; Nurul Kusuma Dewi (Universitas Sebelas Maret, 2018)
The purpose of this research is to apply gardening project method in Kindergarten. Approach to the research using qualitative. Data collection techniques used are observation, interview, and documentation. The technique of testing the validity of data using triangulation is triangulation of sources and technical triangulation. Data analysis technique used is interactive data analysis model. The results explained that the use of gardening project method can be applied in Kindergarten.Them stages of the implementation of the gardening project include: (1) preparatory stage of preparing teaching materials, tools and materials to be used in project activities. (2) Implementation stage is done after the child understands the tasks assigned by the teacher to each group (3) The closing stage has a role as a reinforcing stage in the project activity, ie the child can present the completed project results. Another friend can give an opinion about the work presented and give rewards..